Effect of high Mn content on development of ultra-fine grain extruded magnesium alloy. (15th January 2016) - She, J.; Pan, F.S.; Guo, W.; Tang, A.T.; Gao, Z.Y.; Luo, S.Q.; Song, K.; Yu, Z.W.; Rashad, M.
Abstract: High Mn content added to Mg–6Zn–0.3Ca extruded alloy remarkably refined dynamically recrystallized (DRXed) grains, and enhanced tensile and compressive strengths without sacrificing ductility. The large amount of fine Mn precipitates of homogenized alloy that formed effectively restricted new grain growth during the subsequent extrusion and generated ultra-fine DRXed grains. The ultra-fine DRXed grains and large amount of precipitates essentially enhanced the strength and improved the anisotropy of alloy. The Mg–Mn– x ternary systems that potentially formed ultra-fine grains were also discussed. Graphical abstract: Highlights: High Mn content added to Mg–6Zn–0.3Ca extruded alloy remarkably enhances the strength. Mn precipitate exists before extrusion can remarkably refine DRXed grains. The alloys containing Mn signal phase potentially form ultra-fine DRXed grains.